Dialog Gereja Dengan Komunitas Society Socialis (SOS) Children’s Villages of Flores Waturia-Maumere - Vinsensius M. Junior Situmorang; Astina Vebriani Pasaribu; Fransiskus Bala Kleden; Georgius Ture (JURNAL PASTORAL KATEKETIK, 2025)
This paper examines the role and challenges faced by the SOS Children’s Villages Flores Waturia, Maumere community in providing care for children who have lost parental custody. Children in this community experience various difficulties, particularly in meeting basic needs such as health, education, and psychological and spiritual support. The absence of parents makes them vulnerable to losing direction and hope for the future. On the other hand, limitations in resources, both human and financial, pose serious obstacles in ensuring the provision of adequate care. In this context, the Catholic Church is expected to serve as a strategic partner capable of providing spiritual and moral support. The Church is called not only to provide material assistance but, more importantly, to engage in pastoral services, faith-based accompaniment, and empowerment of the children's potential. Through a humanistic and faith-based approach, the Church can become a transformative force that restores the dignity of children and advocates for their often-overlooked rights. The involvement of the Church is a concrete manifestation of the Christian mission to bring love, justice, and hope to those most in need.